Get up, stand up - Julia, Raul.; DeBeaufort, Marc.; WGBH (Television station : Boston, Mass.); Channel Four (Great Britain); Central Independent Television (South Burlington, VT : Annenberg/CPB Collection, 1993)
This program focuses on the issue of sovereignty of Caribbean and Latin American nations, looks at Jamaica and Colombia. Examines political, economic and social problems in these countries and the effects of intervention by the United States in their affairs.
Title on container: Getup, standup: problems of sovereignty.
In English and Spanish, with English subtitles and voiceovers.
VHS format.
Raul Julia, narrator.
Keywords: Drug traffic -- Colombia; Jamaica -- Politics and government; Jamaica -- Foreign relations -- United States; United States -- Foreign relations -- Jamaica; Jamaica -- Economic conditions; Colombia -- Politics and government -- 1974-; Colombia -- Social conditions; Colombia -- Foreign relations -- United States; United States -- Foreign relations -- Colombia